2007
DOI: 10.1016/j.jcrs.2006.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular lens opacification after nonpenetrating glaucoma surgery with mitomycin-C

Abstract: A 58-year-old woman had successful phacoemulsification with intraocular lens (IOL) implantation in January 2001. Two years later, nonpenetrating glaucoma surgery with mitomycin-C (MMC) 0.02% was performed for uncontrolled glaucoma. Two months later, opacification of the anterior IOL surface was observed. The IOL was removed and a hydrophobic acrylic AcrySof IOL (Alcon) implanted. The opacified IOL was studied by flame atomic absorption spectrometry, which showed the presence of calcium carbonate. A new IOL of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…The anterior findings contrast with the also described "snowflake" or crystalline degeneration of PMMA IOLs, which occurs long-term postoperatively (often a decade or more), and is attributed to manufacturing problems (21). The results of our scanning electron microscopic and Xray spectroscopic analyses coincide with those published in the literature (22)(23)(24), and point to the accumulation of granular deposits composed mainly of calcium, with a quite uniform distribution within the SC60B-OUV (MDR) lens optic and on the surfaces of the other lens models investigated. All attempts to eliminate the deposits causing lens opacification by means of the YAG laser have been unsuccessful; use of the latter should therefore be avoided, and the only valid management option for restoring good patient vision consists of explantation and replacement with a different lens.…”
Section: Discussionsupporting
confidence: 87%
“…The anterior findings contrast with the also described "snowflake" or crystalline degeneration of PMMA IOLs, which occurs long-term postoperatively (often a decade or more), and is attributed to manufacturing problems (21). The results of our scanning electron microscopic and Xray spectroscopic analyses coincide with those published in the literature (22)(23)(24), and point to the accumulation of granular deposits composed mainly of calcium, with a quite uniform distribution within the SC60B-OUV (MDR) lens optic and on the surfaces of the other lens models investigated. All attempts to eliminate the deposits causing lens opacification by means of the YAG laser have been unsuccessful; use of the latter should therefore be avoided, and the only valid management option for restoring good patient vision consists of explantation and replacement with a different lens.…”
Section: Discussionsupporting
confidence: 87%
“…Opacification is related to local agents (viscoelastic devices[13] and mitomycin C)[14] and systemic conditions (diabetes mellitus,[1517] hypertension,[16] ischemic heart disease,[16] and uveitis)[17] among other factors. Histopathologic studies using light microscopy, scanning electron microscopy, and X-ray spectroscopy showed that opacification was caused by granular deposits composed of calcium phosphate hydroxide under the surface of the IOL[18–20] in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…Calcification of intraocular lenses of various IOL materials (silicone [3,7,8], hydrophilic acrylic [9][10][11][12][13][14][15][16], and hydrophobic acrylic [21]) has been reported. Naganome et al [17] reported that the incidence of hydrophilic acrylic IOL calcification was significantly higher than that of other materials.…”
Section: Discussionmentioning
confidence: 99%